Law and administration: meeting and clashes - Bernardo Sordi (Sequência: Estudos Juridicos e Politicos, 2019)
The paper aims to identify the maincharacteristics of the principle of legality duringthe modernity, focusing especially on thedevelopments of continental Europe during the19th century. The author individualizes threemain steps: legality-power, legality-guarantee andlegality-system. The first one happens during theFrench Revolution. The second one spans over theperiod from right after that until mid-nineteenthcentury. The third period starts on mid-nineteenthcentury and goes until the beginning of the 20thcentury. It should be stressed that the differentsteps overlap themselves and leave traces onthe definition of administrative law. Finally, theauthor describes the 20th century, marked by theconstitutionalization of the administration and thereview of the law itself, and the contemporarylegality, marked by stronger demands that gobeyond the simple conformity to the statutory lawto reach the very justification of the administrativeacts.